2005
DOI: 10.1111/j.1440-1754.2005.00687.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral palsy in Victoria: Motor types, topography and gross motor function

Abstract: The VCPR is ideal for population-based studies of gross motor function in children with CP. Gross motor function is similar in populations of children with CP in developed countries but the comparison of motor types and topographical distribution is difficult because of lack of consensus with classification systems. Use of the GMFCS provides a valid and reproducible method for clinicians to describe gross motor function in children with CP using a universal language.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
159
5
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(191 citation statements)
references
References 20 publications
23
159
5
4
Order By: Relevance
“…In the studies of Beckung et al 19 the participants were divided according to motor type and the spastic ones were divided according to topography; quadriplegic spastic ones were all level V, dyskinetic children were classified from level I to V, with a predominance of level III and the ataxic ones were classified in levels I and II; there were no cases of mixed cerebral palsy. himmelmann et al 25 had similar results, in that quadriplegic spastic children were classified in levels IV and V and most of them were level V; diskinetic children were classified in all levels but the majority was levels IV and V. The study of howard et al 16 reported that most of quadriplegic spastic children were level IV and V, diskinetic children were levels II, III and IV and the mixed ones were all levels; the ataxic children were classified in the first three levels and the hypotonic ones were all levels except level II. regarding the relation between motor level and age, our study found a certain tendency to association through Fisher' s exact test (p=0.075) although it did not present significance.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…In the studies of Beckung et al 19 the participants were divided according to motor type and the spastic ones were divided according to topography; quadriplegic spastic ones were all level V, dyskinetic children were classified from level I to V, with a predominance of level III and the ataxic ones were classified in levels I and II; there were no cases of mixed cerebral palsy. himmelmann et al 25 had similar results, in that quadriplegic spastic children were classified in levels IV and V and most of them were level V; diskinetic children were classified in all levels but the majority was levels IV and V. The study of howard et al 16 reported that most of quadriplegic spastic children were level IV and V, diskinetic children were levels II, III and IV and the mixed ones were all levels; the ataxic children were classified in the first three levels and the hypotonic ones were all levels except level II. regarding the relation between motor level and age, our study found a certain tendency to association through Fisher' s exact test (p=0.075) although it did not present significance.…”
Section: Discussionsupporting
confidence: 66%
“…The child was 8 months old and had late development; it is possible that such condition reaches the lowest lower limbs because of its neurological maturation. himmelmann et al 25 found out cases of hemiplegia in all motor levels; Beckung et al 19 established that the cases varied between levels I and IV; howard et al 16 found levels I, II, III and V and Voorman et al 18 classified the cases under levels I, II and III. diplegic children in this study were similar (with no significant difference) in the first four levels and there were no examples of level V; in their study Voorman et al 18 had the same results and only 3 cases (6.4%) were level V. In their study himmelmann et al 25 had diplegic children in all levels, most of them were level II (37.5%) and only 4.9% of the children were classified in level V. Similar results were found in the study of Beckung et al 19 in which they observed that most children were classified in the first two levels while only 4% were classified in level V. The results in the study of howard et al 16 were very similar in the first three levels; only 4 cases (5%) were level IV and no diplegic children were level V.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 For this study we took advantage of data from two prospective longitudinal studies of gross motor development of children with CP. Although one study is a clinic-based cohort in the Netherlands (PERRIN CP 0)5 study) and the other a population-based study in Canada (OMG study) the distribution over the five GMFCS levels is good, representing the spectrum of severity in CP as seen in larger population based studies 16,17 The inclusion of children from North America and Europe and their distribution over the five levels of the GMFCS provides preliminary evidence that the findings can be generalized to all children with CP less than 2 years of age. We did not study the interrater reliability of the GMFCS in this study, but as reclassifications were seen both in children classified by the same observer and in children classified by different observers at Time 1 and Time 2, we do not think that this has influenced our results.…”
Section: Movements In and Outmentioning
confidence: 99%
“…Quanto à realização de tarefas cognitivas e comportamentais, os hemiplégicos também apresentaram os melhores resultados nas análises de Scheffe e Posthoc 27 .…”
Section: Funcionalidadeunclassified